Formação continuada de docentes dos anos iniciais da rede estadual de Ariquemes, Rondônia: um diferencial na qualidade no ensino numa perspectiva emancipatória - Klein, Mônica Inacio (2013)
The Continuing Education has become indispensable for the pursuit of quality education in the country, although many teachers still resist the practice. This study is the result of the analysis of the results of external evaluations and teaching practice guided by evaluative analyzes and reflections on improving the quality of education from the insertion of continuing education in school daily life. Therefore, we sought to evaluate by literature and documents the vision of the authors in relation to the concepts of continuing education, as well as the reflections of the results reached in external evaluations. This work is structured in three chapters. The first chapter presents and discusses from the point of view of many authors historical concepts of education in Brazil and continuing education. Chapter two discusses the quality of teaching and assessment in the context of continuing education, focusing on the external evaluation, as well as introduces and characterizes this matrices that guide these evaluations. Chapter three presents as a parameter to the profile analysis and discussion of the state schools in the city of Porto Velho and results IDEB. After characterization of the schools, it is reported as it was inserted in these schools of continuing education and continuing education pro-literacy, as well as discussion and reflection on the importance of this. The results obtained through the object of research show that continuing education can contribute to significant changes in teaching practice and the teaching quality, and may be for either local or national, because this makes the act of teaching a constant reflection of practice, evaluation of results achieved and change in teaching practice.